If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 137 + -1(6x + 5) = 6(x + 9) + x Reorder the terms: 137 + -1(5 + 6x) = 6(x + 9) + x 137 + (5 * -1 + 6x * -1) = 6(x + 9) + x 137 + (-5 + -6x) = 6(x + 9) + x Combine like terms: 137 + -5 = 132 132 + -6x = 6(x + 9) + x Reorder the terms: 132 + -6x = 6(9 + x) + x 132 + -6x = (9 * 6 + x * 6) + x 132 + -6x = (54 + 6x) + x Combine like terms: 6x + x = 7x 132 + -6x = 54 + 7x Solving 132 + -6x = 54 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 132 + -6x + -7x = 54 + 7x + -7x Combine like terms: -6x + -7x = -13x 132 + -13x = 54 + 7x + -7x Combine like terms: 7x + -7x = 0 132 + -13x = 54 + 0 132 + -13x = 54 Add '-132' to each side of the equation. 132 + -132 + -13x = 54 + -132 Combine like terms: 132 + -132 = 0 0 + -13x = 54 + -132 -13x = 54 + -132 Combine like terms: 54 + -132 = -78 -13x = -78 Divide each side by '-13'. x = 6 Simplifying x = 6
| 2/3x–6=9 | | 5x-4=x+3*2 | | 5[2-g]=0 | | 14=3m+5 | | 5+6=4+Y | | 10[1-2y]=-5[2y-1] | | -3sin(t)+2cos(t)=0 | | 3(3+2x)-4x=59-3x | | 15z-2=(2z+3) | | 3x-(12x-x)=5+2(x-1)-1 | | 3y+5y+2y= | | 6r-6=72-6 | | 5n-30=20 | | 3x-(12-x)=5+2(x+1)-1 | | 5y=11x-7 | | 3(x+5)-2=6x-3(-4+x) | | -8x+3=25 | | 5y=11x+7 | | LNx=-1.6 | | Log(8x-7)/log(x) | | -6f+13=-9z+24 | | 9(5+x)=8(x-4) | | 5+2X=14-4N | | 4y-13=43 | | -8b/5=-1 | | 4x-38=9x-3 | | 5x+39=154 | | 6+65x=52x+18 | | x-5x^(1/2)-6=0 | | 2.6(x-0.8)=9 | | 7(y+6)=3+6y | | 6+65x=52+18 |